Inter-site variation in allometry and wood density of goupia glabra aubl. In amazonia - Siliprandi, N. C.; Nogueira, Euler Melo; Toledo, Jos? Julio; Fearnside, Philip Martin; Nascimento, Henrique Eduardo Mendonça (Revista Brasileira de Biologia, 2016)
The present study aims to compare the allometry and wood density of Goupia glabra Aubl. (Goupiaceae) in two different terra-firme sites in Amazonian forest. A total of 65 trees ≥ 10 cm DBH was sampled in both sites, with 39 trees in Nova Olinda do Norte (NOlinda, near the Amazon River) and 29 trees in Apui (near the southern edge of the Amazon forest). Except for the relationship between DBH (diameter at breast height) and Ht (total height), allometric relationships for G. glahra differed significantly between sites. Apui had lower intercept and greater slope for log10 (DBH) versus log10 (Hs - stem height), and, conversely, greater intercept and lower slope for log10 (DBH) versus log10 (Ch - crown height). The slope differed significantly between the sites for DBH versus Cd (crown diameter), with greater slope found for NOlinda. Mean basic wood density in Apui was 8.8% lower than in NOlinda. Our findings highlight the variation in adaptive strategy of G. glabra due to environmental differences between sites. This is probably because of different canopy-understory light gradients, which result in differentiation of resource allocation between vertical and horizontal growth, which, in turn, affects mechanical support related to wood density. We also hypothesize that differences in soil fertility and disturbance regimes between sites may act concomitantly with light. © 2016, Instituto Internacional de Ecologia. All rights reserved.
Variação entre-sftios na alometria e densidade da madeira de Goupia glabra Aubl. Na Amazônia
Keywords: Soil; Anatomy And Histology; Angiosperm; Chemistry; Forest; Growth, Development And Aging; Light; Soil; Wood; Angiosperms; Forests; Light; Soil; Wood